Breaking free from chemical spreadsheets. Issue 9 (September 2015) - Segall, Matthew; Champness, Ed; Leeding, Chris; Chisholm, James; Hunt, Peter; Elliott, Alex; Garcia-Martinez, Hector; Foster, Nick; Dowling, Samuel
Highlights We think about compounds and data in terms of groups and relationships. Chemoinformatics methods help to find important patterns in compound data. Chemical spreadsheets make it difficult to work within these frameworks. New visual approaches represent compound data in context and facilitate interaction. Intuitive understanding of patterns and SAR guides further compound optimisation.